Microalgal biomass with high potential for the biofuels production - Jimenez Escobedo, Manuel (2021)
The study of biofuels continues in constant development, for five decades. This article summarizes the analysis of several recent scientific publications, related to third generation biofuels using microalgae. An overview of biofuels and their classification, the theoretical bases of microalgae, techniques for their cultivation, harvesting and pretreatment of their biomass are presented. Promising technologies for obtaining biofuels of great potential worldwide demand are also briefly described, considering the technical characteristics of the process, depending on the microalgae species that have the highest yields and productivity for each type of biofuel: Biodiesel (extraction of lipids, transesterification and purification), ethanol (hydrolysis of sugars, fermentation and purification) and biogas (anaerobic digestion). Most studies are focused on the production of lipids, being Chlorella vulgaris, Nanochloropsis sp. and Botryococcus braunii (A) the most used microalgae to obtain biodiesel. However, there are few studies focused on the production of microalgal biomass to produce bioethanol, thus, the microalgae Porphyridium cruentum and Spirogira sp. they could be used to produce bioethanol, with the advantage of not containing lignin. Biogas is produced by anaerobic biodigestion of microalgal biomass residues in biorefineries, but its commercial production is very limited due to high production costs and because there are other economically very competitive biomasses. The need to produce biofuels using microalgal biomass is reaching a greater boom, the transcendental proposal being the launching of a biorefinery, mainly focused on the optimal production of microalgal biomass as the main key to the entire process.